Debito pubblico, ricchezza privata e politiche per la famiglia - Cigno, Alessandro (Lectio Magistralis, 2012)
What is the relationship between public debt and private wealth? And what do family policies have to do with these financial aggregates? We will see that there is a connection, but let's first clarify what is meant by family. In the common sense, a family includes ascenders, descendants and collaterals. But when we talk about family policies we only think of potential parents or families with pre-school children.